PENGARUH CITRA MEREK, WORD OF MOUTH DAN KETEPATAN WAKTU PENGIRIMAN TERHADAP MINAT BELI KONSUMEN DENGAN KEPERCAYAAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA YASAKA FRIED CHICKEN SITUBONDO - Faris Zainul Anwar; Mohammad Yahya Arief; Riza Rachman (Fakultas Ekonomi dan Bisnis, 2025)
The purpose of this study is to determine the Influence of Brand Image, Word Of Mouth and Timeliness of Delivery on Consumer Purchase Interest with Consumer Trust as an Intervening Variable at Yasaka Fried Chicken Situbondo. The sampling technique used in this study was simple random sampling of 98 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the study showed that Brand Image has a significant positive effect on Consumer Trust, Word Of Mouth has a significant positive effect on Consumer Trust, Timeliness of Delivery has a significant positive effect on Consumer Trust, Brand Image has a significant positive effect on Consumer Purchase Interest, Word Of Mouth has a significant negative effect on Consumer Purchase Interest, Timeliness of Delivery has a positive but not significant effect on Consumer Trust, Consumer Trust has a significant positive effect on Consumer Purchase Interest, Brand Image has a significant positive effect on Consumer Purchase Interest, Consumer purchase through Consumer Trust, Word Of Mouth has a significant positive effect on Consumer Purchase Interest through Consumer Trust, Timeliness of Delivery has a significant positive effect on Consumer Purchase Interest through Consumer Trust.